Magnesium Particles Coated with Mesoporous Nanoshells as Sustainable Therapeutic‐Hydrogen Suppliers to Scavenge Continuously Generated Hydroxyl Radicals in Long Term. (18th December 2018) - Kong, Lei; Chen, Chuanrui; Mou, Fangzhi; Feng, Yizheng; You, Ming; Yin, Yixia; Guan, Jianguo
Abstract: Sustainable supplementation of massive molecular‐H2 is considered to be the most effective therapy for long‐term elimination of excessive hydroxyl radicals (·OH) in vivo, but has not been achieved so far. In this work, it is demonstrated that magnesium microparticles (Mg MPs) coated with mesoporous nanoshells can achieve the long‐term and high‐efficient generation of therapeutic hydrogen in physiological condition for ·OH scavenging. The as‐proposed magnesium@mesoporous SiO2 core–shell microparticles (Mg@p‐SiO2 MPs) are synthesized by developing a modified Stöber method using acetone as the solvent, and they exhibit shell thickness ( d )‐dependent H2 release behavior due to the barrier effect of nanoshells on both the occurrence of Mg–water reaction and H2 diffusion. Consequently, they are able to provide vast quantities of H2 molecules dissolved in body fluid with a rate controlled by d over a long period. A simulation model is established which well explains and further predicts the dependence of H2 release behavior on d, and the long‐term protection of cells from oxidative damage by Mg@p‐SiO2 MPs is also experimentally validated. As the H2 concentration and effective duration in medium can be adjusted by dosage and d, Mg@p‐SiO2 MPs are promising for accurate H2 drug delivery in vivo. Abstract : The magnesium@mesoporous SiO2 core–shell microparticles (Mg@p‐SiO2 MPs) can achieve the long‐term and high‐efficient generation of therapeutic hydrogen in physiological condition for ·OH scavenging, which are synthesized by developing a modified Stöber method using acetone as the solvent and protect cells from oxidative damage for a long time.